2017
DOI: 10.1080/00221546.2017.1390970
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to Underprepared First-Time-in-College Students When Developmental Education is Optional? The Case of Developmental Math and Intermediate Algebra in the First Semester

Abstract: In 2014, developmental education became optional for many college students in Florida, regardless of prior academic preparation. This study investigated first-semester math course enrollment patterns for underprepared first-time-in-college (FTIC) students who would have previously been required to take developmental math and the passing rates for the students electing to take Intermediate Algebra (the most common gateway math course in Florida). We found that roughly a 3rd of underprepared students enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Of our sample, 91.5% enrolled in English Composition 1 and 54.8% enrolled in Intermediate Algebra. The low math course-taking rate aligns with previous research that given the option, students may choose to enroll in developmental math or delay enrollment in any math course (Park, Woods, Hu, Bertrand Jones, & Tandberg, 2017;Park et al, 2016;.…”
Section: Data and Samplesupporting
confidence: 76%
“…Of our sample, 91.5% enrolled in English Composition 1 and 54.8% enrolled in Intermediate Algebra. The low math course-taking rate aligns with previous research that given the option, students may choose to enroll in developmental math or delay enrollment in any math course (Park, Woods, Hu, Bertrand Jones, & Tandberg, 2017;Park et al, 2016;.…”
Section: Data and Samplesupporting
confidence: 76%
“…There is emerging research investigating the unique version of selfplacement being implemented in Florida under SB 1720, which allows students to ''opt-out'' of remediation. Findings thus far indicate that after the policy shift in 2014, significantly more students took the gateway math courses required for college graduation but pass rates in these courses declined (Hu et al, 2016;Park et al, 2018). But researchers also found that a greater number of students ultimately completed the math required for college graduation.…”
Section: Prior Research On Self-placementmentioning
confidence: 99%
“…Thus, DSP may actually generate worse outcomes than placement testing if it encourages certain student groups to select a less rigorous course than they would have otherwise qualified for, which risks unnecessarily lengthening the amount of time needed to earn a degree. Indeed, Park et al (2018) noted equity concerns with Florida’s self-placement policy, since Black students and female students were less likely to enroll in gateway math courses than White and male students, respectively. Again, whether this is attributable to the policy itself or merely to demographic changes in the college student population is unknown.…”
Section: Prior Research On Self-placementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no indication that these findings have changed since. Eliminating developmental courses and requiring co-requisite supplemental classes or the completion of computer-assisted modules are other trends in supporting under-prepared students (see, e.g., [14], [17]). Even if such courses are eliminated, it is left to the mathematics professor to prepare students who are not yet ready for college-level classes so they can advance and earn their undergraduate degrees.…”
mentioning
confidence: 99%